2020
DOI: 10.3389/fimmu.2019.03028
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Severity and Its Impact on Local Inflammation in Extremity Injury—Insights From a Combined Trauma Model in Pigs

Abstract: Background: Extremity fracture is frequently seen in multiple traumatized patients. Local post-traumatic inflammatory reactions as well as local and systemic interactions have been described in previous studies. However, trauma severity and its impact on the local immunologic reaction remains unclear. Therefore, fracture-associated local inflammation was investigated in a porcine model of isolated and combined trauma to gain information about the early inflammatory stages. Material and Methods: Polytrauma (PT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…Muscle tissue provides bones with oxygen, nutrients, and osteoprogenitor cells, but it also seems critical for bone healing due to its immunological potential. In this context, the humeral response in the musculature has been shown to be in uenced by trauma severity and by the strategy used for fracture xation, indicating a potential effect of muscle on the early phase of fracture healing [18]. In the current study, we focused on changes in PMNL in ltration to assess the cellular aspects of the muscular immune response and to elucidate the role of both concomitant injuries and the strategy of fracture xation in a translationally relevant, long-term pig model.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle tissue provides bones with oxygen, nutrients, and osteoprogenitor cells, but it also seems critical for bone healing due to its immunological potential. In this context, the humeral response in the musculature has been shown to be in uenced by trauma severity and by the strategy used for fracture xation, indicating a potential effect of muscle on the early phase of fracture healing [18]. In the current study, we focused on changes in PMNL in ltration to assess the cellular aspects of the muscular immune response and to elucidate the role of both concomitant injuries and the strategy of fracture xation in a translationally relevant, long-term pig model.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle tissue provides bones with oxygen, nutrients, and osteoprogenitor cells, but it also seems critical for bone healing due to its immunological potential. In this context, the humeral response in the musculature has been shown to be in uenced by trauma severity and by the strategy used for fracture xation, indicating a potential effect of muscle on the early phase of fracture healing [11]. In the current study, we focused on changes in PMNL in ltration to assess the cellular aspects of the muscular immune response and to elucidate the role of both concomitant injuries and the strategy of fracture xation in a translationally relevant, long-term pig model.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, for fracture hematoma it was shown that it might have different cytokine patterns then other fracture surrounding tissues and thus also different cellular compositions than those in the muscle tissue [11]. Consequently, in addition to the musculature, the fracture hematoma and maybe additional soft tissues are also of particular importance for trauma outcome.…”
Section: Introductionmentioning
confidence: 99%
“…During fracture healing, the local fracture hematoma at a fracture site is rich in multiple cytokines, in ammatory factors, and many kinds of cells, which are helpful for bone and soft tissue repair [6]. Horst et al [7] pointed out that there was evidential up-regulation of the concentrations of interleukin-6 (IL -6) and interleukin-8 (IL-8) in fracture hematomas when compared with the serum values in a combined trauma pig model. According to previous studies, IL-6 and IL-8 obviously affect the osteoblastogenesis and osteoclastogenesis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Horst et al [7] pointed out that there was evidential up-regulation of the concentrations of interleukin-6 (IL -6) and interleukin-8 (IL-8) in fracture hematomas when compared with the serum values in a combined trauma pig model. According to previous studies, IL-6 and IL-8 obviously affect the osteoblastogenesis and osteoclastogenesis [7][8][9][10]. Interleukin-34 (IL-34), a newly discovered cytokine, showing capable of inducing pro-in ammatory cytokines and chemokines such as IL-6 and IL-8 [11].…”
Section: Introductionmentioning
confidence: 99%